Soft-bottom polychaetes from the Brazilian harbors of mucuripe and Pecém (State of Ceará) and Santos (State of São Paulo) - Buruaem, Lucas Moreira [UNESP]; Petti, Mônica Angélica Varella; De Souza Abessa, Denis Moledo [UNESP] (My University, 2015)
The analysis of polychaete fauna from 20 softbottom samples collected in different shallow sectors of Mucuripe, Pecém and Santos harbors provided a list of 34 different taxa, totaling 366individuals. A comparison with recent published data revealed the first occurrence of two polychaete genera and 10 species in Ceará state. Distribution by station, depth and type of sediment was also provided. Despite the considerable knowledge of polychaete fauna from the coast of Brazil especially in the southeastern region, little attention has been given to the harbor areas, which are under influence of anthropogenic impacts. This study represents an important inventory of polychaete fauna found in three harbors from the northeastern (Mucuripe and Pecém, State of Ceará) and southeastern (Santos, state of São Paulo) regions of Brazilian coast.
Keywords: Annelida; Benthos; Biodiversity; Macroinfauna; Tropical environments